Specification for nickel-alloy electrodes for flux cored arc welding (American Welding Society, 2013)
"The composition, soundness, and properties of weld metal from ten grades of flux cored electrodes are specified. Standard electrode sizes together with their package forms and package sizes are detailed. This specification makes use of both U.S. Customary Units and the International System of Units (SI). Since these are not equivalent, each system must be used independently of the other."
"AWS A5.34/A5.34M:2013, an American National Standard."
"Approved by the American National Standards Institute, July 29, 2013."
"Supersedes AWS A5.34/A5.34M:2007."
Keywords: Electric welding -- Specifications.; Nickel -- Welding.; Nickel alloys -- Welding.; Electrodes, Nickel -- Specifications.; elektronické knihy; electronic books